Synthesis of Gold Nanoparticles in Presence of Ionic Liquid [Bmin][CF3SO3] with Humic Acid under Microwave Irradiation and Its Application as a Nanocatalyst - Eon Lee, Seong; Won Ko, Jeong; Bae Ko, Weon (Asian Journal of Chemistry, 2013)
Gold nanoparticles were synthesized in the presence of ionic liquid [Bmin][CF3SO3] with humic acid for 90 s under microwave irradiation. The resulting gold nanoparticles were confirmed by UV-visible spectroscopy, X-ray diffraction and transmission electron microscopy. The catalytic effect of gold nanoparticles was investigated for the oxidation of 2-hydroxybenzyl alcohol to produce 2-hydroxybenzaldehyde in the presence of 3-chloroperoxybenzoic acid and hydrogen peroxide in methanol. The reaction was completed after 160 min using these gold nanoparticles as a catalyst and the product was identified by high performance liquid chromatography (HPLC) with UV-visible detector.